'The Color imagery in the poetry of Fityan Al-Shaghuri - AL-Wa'ily, Kholoud Hashim Juhi (Al-Adab Journal, 2019)
Colors, shapes and types are divine miracles. This variation in colors in the universe and nature shows the differences in the creation of all the creatures. These features were reflected in great presence as well as other sources that manifest in women, wine, gray hair, wars and their tools in the poetic imagination of the Fityan Al- Shaghury. Therefore, this poet produced the finest poetic color images and showed these colors beautifully through symbol and inspiration as a sign of meanings that paints beautiful meanings that the readers agrees with it as being is familiar in the lives of people. Other mentions of the poet manifest in the paradoxes of artistic images of beautiful colors as the point where the base of the rhetorical styles that are combined to form these images, especially metaphor, anaphylaxis, antonomasia, implicit metaphor and diagnostic and visual visions, that had a clear effect in his images, which contribute to the level of rhythmic activity in the creative color imagery.